Starting age and other influential factors: Insights from learner interviews - Muñoz, Carmen (Studies in Second Language Learning and Teaching, 2014)
The present study uses oral interviews with foreign language learners in search of influential factors in their language learning histories. The sample for the study was drawn from a larger sample of intermediate/advanced learners of English as a foreign language with a minimum of 10 years of exposure/instruction. The sample includes 6 early learners (range of starting age: 3.2-6.5) and 6 late learners (starting age: 11+). Half of them in each group were among those with the highest scores on two English language tests in the larger sample and half among those with the lowest scores on those same tests. A qualitative analysis of the interviews of these learners yields insights into their experience of foreign language learning and the role played in it by starting age and other significant factors, such as motivation and intensive contact with the language.